(untitled) (American Journal of Islam and Society, 2006)
On 10 August 2006, The National Advisory Council for South Asian Affairs (NACSAA) met at the Cosmos Club in Washington, DC, to answer several questions: Do markets know best? Does the market really know? Are the rich getting richer and the poor getting poorer? Does globalization mean Westernization and/or Americanization? Are traditional societies being dissipated? As there were many speakers, I will present only brief summaries. Shabir Ahmed stated that the West uses its foreign aid to get countries to follow its own standards and perspectives, while many members of the elites have abandoned the traditional lifestyle. On the positive side, globalization solves poverty through the market. Syed Akhtar asked whether globalization was the same as McDonaldization or Nikeification, or just about cultural domination and sweatshops. He sees globalization as a win-win situation, provided that a nation has the necessary “enabling conditions”: a highly educated workforce, the rule of law, and democratic institutions. V. Balachandran reminded the audience that globalization also causes problems. In India, this takes the form of increasing farmer suicides, shanty towns, a lack of investment in the agricultural sector, a decrease in the quality of life, and questions of who owns the country’s natural resources. James Clad defined globalization in negative terms: It is not necessarily an acrossthe- board integration of economies, a generator of an immediately improved security environment, a trend of deepening skill sets and the development of an industrial and an R&D culture, something new (it is a recurrent phenomenon enabled by technological advancement), or westernization, for all cultures borrow what is useful to them. Abdul Mommen claimed that the South Asian diaspora can help root out terrorism. Currently, South Asia is facing higher levels of terrorism; in America and western Europe, these levels are actually declining or increasing only marginally. Bangladesh, despite being a liberal Muslim state, is seeing its level of terrorism, as well as the number of fatalities, grow even faster than has been the case in the Middle East since 9/11. Vijay Sazawal spoke on self-governance and trans-nationalism in Kashmir. He pointed out that while Pakistan calls for more self-rule in Indian Kashmir, it provides almost none to its own Kashmiri citizens. He concluded that “the line of control (LOC) is more or less a pretty clean division between various ethnic entities that make up the old princely state and that the current boundary can sustain regional stability even when its political future is questioned.” ...